The Idea of "India" and "Gandāra" in the Earliest Iranian and Greek Sources. - KING, RHYNE; COLLETT, ALICE (Journal of the American Society for Premodern Asia (JASPA))
Hinduš, the Old Persian name for a region of the Achaemenid Persian Empire (550–330 bce), ultimately underlies the English word India. The history of the word Hinduš and its cognates has attracted considerable research, yet the precise referent of Hinduš in its Achaemenid context remains imperfectly understood. Achaemenid sources often group Hinduš together with the neighboring region of Gandāra, and analyzing the two regions together is key to understanding them. In this article we reassess the earliest appearances of Hinduš, Gandāra, and their cognates in the Iranian and Greek sources. We first demonstrate that Achaemenid knowledge of South Asia was vague, and although imperial administrators broadly located Hinduš in the lower Indus and Gandāra in the upper Indus, they did not use these toponyms entirely consistently. Next, we turn to the Classical Greek sources. The Greeks recognized Gandāra as a far eastern region of the Achaemenid Empire, but they expanded the idea of Hinduš, as Indikḗ, into a fantastical land on the edge of the world.